A systematic review on the mechanisms of vitamin K effects on the complications of diabetes and pre‐diabetes. (1st October 2019) - Karamzad, Nahid; Maleki, Vahid; Carson‐Chahhoud, Kristin; Azizi, Samaneh; Sahebkar, Amirhossein; Gargari, Bahram Pourghassem
Abstract: Diabetes mellitus and pre‐diabetes are prevalent endocrine disorders associated with substantial morbidity and premature mortality. Vitamin K is known to have several beneficial effects on complications of diabetes and pre‐diabetes. However, systematic consolidation of evidence is required to quantify these effects in order to inform clinical practice and research. A systematic search in PubMed, Scopus, Embase, ProQuest, and Google Scholar databases was undertaken from database inception up to October 2018 to evaluate functional roles of different forms of vitamin K on diabetes and pre‐diabetes. From 3, 734 identified records, nine articles met the inclusion criteria and were evaluated. Vitamin K supplementation was found to be associated with significant reductions in blood glucose (six studies), increased fasting serum insulin (four studies), reduced hemoglobin A1c (three studies), reduced homeostatic model assessment‐insulin resistance index (HOMA‐IR) (two studies), and increased ß‐cell function (two studies) in diabetic animal studies. Following 2‐hour oral glucose tolerance test, vitamin K supplementation was observed to be effective in reducing blood glucose and insulin levels in the pre‐diabetic population. However, no evidence of effect was observed for fasting blood sugar, insulin, HOMA‐IR, and homeostatic model assessment‐β‐cell function index (two studies). A statistically significant effect was also noted with vitamin K in improving dyslipidemia (three studies) as well as oxidative stress and inflammatory markers (five studies) in diabetic animals. In conclusion, clinical trials and animal studies confirm that vitamin K supplementation may improve both clinical features and complications of diabetes and pre‐diabetes. However, quantification of clinical efficacy in the pre‐diabetic population and among individuals with comorbidities requires further investigation.